Private branch exchanges for connection to public switched telephone networks run by certain public telecommunication operators.Facilities on private branch exchanges. Specification for facilities on private branch exchanges with terminating stations treated as an entirety Part 5-5.1, (30th September 1988) - British Standards Institution,
No abstract available